A Multicenter Observational Study of Family Participation in ICU Rounds. Issue 8 (August 2018) - Au, Selena S.; Roze des Ordons, Amanda L.; Parsons Leigh, Jeanna; Soo, Andrea; Guienguere, Simon; Bagshaw, Sean M.; Stelfox, Henry T.
Abstract : Objectives: Guidelines recommend offering family members of critically ill patients the option to attend interdisciplinary team rounds as a way to improve communication and satisfaction. Uncertainty remains around the benefits and risks. Design: We conducted an observational study to describe family participation in ICU rounds and its association with rounding processes. Setting: Rounds conducted under the leadership of 33 attending physicians in seven hospitals across three Canadian cities. Patients: Three hundred two individual rounds on 210 unique patients were observed. Interventions: Quantitative and qualitative data were collected using standardized observational tools. Measurements and Main Results: Among the 302 rounds observed, family attended in 68 rounds (23%), were present in ICU but did not attend in 59 rounds (20%), and were absent from the ICU in 175 rounds (58%). The median duration of rounds respectively for these three groups of patients was 20 minutes (interquartile range, 14–26 min), 16 minutes (interquartile range, 13–22 min), and 16 minutes (interquartile range, 10–23 min) ( p = 0.01). There were no significant differences in prognostic discussions (35% vs 36% vs 36%; p = 0.99) or bedside teaching (35% vs 37% vs 34%; p = 0.88). The quality of rounds was not significantly associated with family attendance in rounds or presence in the ICU (quality score [1 (low) to 10 (high)] median 8 [interquartile range, 7–8] vs 7 [interquartile range, 6–9] vs 7 [interquartile range, 6–9]; p = 0.11). Qualitative analyses suggested that family attendance may influence relationship building, information gathering, patient and family education, team dynamics, future family meetings, workflow, and shared clinical decision-making. Conclusions: Our results suggest family attendance in ICU rounds is associated with longer duration of rounds, but not the frequency of trainee teaching, discussions of prognosis, or quality of rounds. Family attendance in rounds may enhance communication and complement family conferences. Abstract : Supplemental Digital Content is available in the text.